PENGARUH KEDEKATAN ORANG TUA, SIKAP PERCAYA DIRI DAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR IPS - Ridhaningtyas, Latifa Putri; Sunarso, Ali; Suratno (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This study aims to examine the impact of parental closeness, self-confidence, and learning independence on social studies learning outcomes. The research method used was a survey with a correlational approach. The study population consisted of 137 elementary school students, with a sample of 102 students from 3 public elementary schools in Mijen Subdistrict, Semarang. The results showed the following: First, there is a significant influence between parental closeness and learning outcomes, which can be confirmed through t-test with the result (0.817 > 0.195). Second, there is a significant influence between Confident Attitude and learning outcomes, which can be confirmed through the t test with the results (0.719 > 0.195). Third, there is a significant influence between Learning Independence and learning outcomes, which can be confirmed through the t test with the results (0.719 > 0.195). Fourth, there is a significant influence between Parental Closeness (X1), Confident Attitude (X2), and Learning Independence (X3) together on social studies learning outcomes (Y), which can be confirmed through the t test with the results (0.548 > 0.195). Keywords: Parental Attachment; Self-Confidence; Learning Independence